2017
DOI: 10.1021/jacs.7b01833
|View full text |Cite
|
Sign up to set email alerts
|

Rh2(II)-Catalyzed Ring Expansion of Cyclobutanol-Substituted Aryl Azides To Access Medium-Sized N-Heterocycles

Abstract: A new reactivity pattern of Rh(II)-N-arylnitrenes was discovered that facilitates the synthesis of medium-sized N-heterocycles from ortho-cyclobutanol-substituted aryl azides. The key ring-expansion step of the catalytic cycle is both chemoselective and stereospecific. Our mechanistic experiments implicate the formation of a rhodium N-arylnitrene catalytic intermediate and reveal that sp C-H bond amination of this electrophilic species is competitive with the ring-expansion process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…A report by Driver and co-workers on the Rh(II)-catalyzed ring expansion of cyclobutanols was found to be compatible with cyclopropyl alcohols (Scheme 134). 312 Here, aryl azide 632 could be converted to N-heterocycle 633 in 80% yield in the presence of catalytic Rh 2 (esp) 2 ( Cha and co-workers reported the synthesis of spirocyclobutanone 641 as a precursor to eight-membered carbocycles (Scheme 135). 313,314 The authors found that, by treating cyclopropyl silyl ether 639 and bromoacetal 640 in the presence of TiCl 4 (1.5 equiv), cyclobutanone 641 was produced in 71% yield and 5:3 dr for the cis stereoisomer via a vinylogous Mukaiyama condensation with intermediate oxocarbenium species 642 (Scheme 135a).…”
Section: Ring Opening Of Cyclopropyl Alcohols With Lewis Acidsmentioning
confidence: 59%
“…A report by Driver and co-workers on the Rh(II)-catalyzed ring expansion of cyclobutanols was found to be compatible with cyclopropyl alcohols (Scheme 134). 312 Here, aryl azide 632 could be converted to N-heterocycle 633 in 80% yield in the presence of catalytic Rh 2 (esp) 2 ( Cha and co-workers reported the synthesis of spirocyclobutanone 641 as a precursor to eight-membered carbocycles (Scheme 135). 313,314 The authors found that, by treating cyclopropyl silyl ether 639 and bromoacetal 640 in the presence of TiCl 4 (1.5 equiv), cyclobutanone 641 was produced in 71% yield and 5:3 dr for the cis stereoisomer via a vinylogous Mukaiyama condensation with intermediate oxocarbenium species 642 (Scheme 135a).…”
Section: Ring Opening Of Cyclopropyl Alcohols With Lewis Acidsmentioning
confidence: 59%
“…N ‐(2‐Bromo‐4‐methylphenyl)formamide [19b] ( 3 l ): Using the experimental procedure EP‐1 , the product was obtained as off‐white solid in 78 % yield. A mixture of rotamers is observed; 1 H NMR (400 MHz, CDCl 3 ) δ 8.62 (d, J =11.2 Hz, 0.35H), 8.45 (s, 0.66H), 8.22 (d, J =8.3 Hz, 0.66H), 7.62 (br, s, 0.82H), 7.42 (s, 0.48H), 7.36 (s, 0.49H), 7.12 (t, J =8.8 Hz, 1.32H), 2.30 (d, J =7.8 Hz, 3H).…”
Section: Methodsmentioning
confidence: 99%
“…The ring-strain of small carbocycles was also exploited by Driver and co-workers to construct benzazepinones 128 from cyclobutanol-substituted aryl azides 126 (Scheme 25). 50 The authors were curious to find whether a new reactivity pattern of metal N-aryl nitrene 127 might be realized by leveraging the ring strain in cyclobutanol to construct medium-ring N-heterocycles. After screening a series of established N-atom transfer catalysts, the authors determined that 1 mol% of Rh 2 (esp) 2 efficiently transformed aryl azide 126 into benzazepinone 128.…”
Section: Short Review Synthesismentioning
confidence: 99%